The role of affect in pacing: experimental study - Serrano-Ibáñez, Elena R.; Condor, María; Marcos, Estefanía; Ramírez-Maestre, Carmen; López-Martínez, Alicia E.; Esteve, Rosa (Anales de Psicología / Annals of Psychology, 2022)
People with chronic pain often change the way they carry out their daily activities according to different patterns, among which are pacing strategies. Cross-sectional studies on the association between pacing and affect show contradictory results. The study aim was to experimentally test whether the induction of positive affect vs negative affect would influence the choice of the type of pacing (pacing to increase productivity or pacing to reduce pain) when the participants were exposed to pain, while controlling for the variables optimism and catastrophism. The study participants comprised a sample of 145 undergraduates. The results of multinomial logistic regression showed that there was no association between the variables. Pacing is an intervention strategy in all chronic pain intervention models, and thus it is relevant to continue investigating the role of affect in relation to pacing.